Evaluation of low cryptococcal antigen titer as determined by the lateral flow assay in serum and cerebrospinal fluid among HIV-negative patients: a retrospective diagnostic accuracy study - Xuan Wang; Jia-Hui Cheng; Ling-Hong Zhou; Jun-Hao Zhu; Rui-Ying Wang; Hua-Zhen Zhao; Ying-Kui Jiang; Li-Ping Huang; Ching-Wan Yip; Chun-Xing Que; Min Zhu; Li-Ping Zhu (IMA Fungus)
Abstract Cryptococcosis is one of the most common opportunistic infections in both immunocompetent and immunocompromised hosts. Although the cryptococcal antigen (CrAg) lateral flow assay (LFA) has been widely used in clinical settings due to its high sensitivity and specificity, the diagnostic value of a low CrAg LFA titers remains unclear. In this study, we performed a retrospective analysis of 149 HIV-negative patients with low CrAg LFA titers (≤1:10) in a Chinese tertiary hospital from January 2013 to December 2017, to evaluate the diagnostic value of low CrAg LFA titers in serum and cerebrospinal fluid (CSF) at different thresholds. Sensitivity and specificity of low CrAg LFA titers in patients with definitive diagnoses of cryptococcosis were 39.6% (95% CI, 29.7–50.1%) and 100% (95% CI, 69.2–100%), respectively, at a threshold of 1:10 in serum. A sensitivity of 72.9% (95% CI, 62.9–81.5%) and a decreased specificity of 70.0% (95% CI, 34.8–93.3%) were observed at a threshold of 1:5 in serum. No false-positive cases were identified in patients with low CrAg titers in CSF and all positive predictive values (PPVs) were 100%. Among the cases with low serum CrAg titers, lumbar puncture was performed in 97 patients and positive CSF CrAg titers were reported in 6 patients. In conclusion, the results of this study imply that low CrAg LFA titer, either in serum or CSF, is crucial for early diagnosis of cryptococcosis in HIV-negative patients, and lumbar puncture is recommended to be performed routinely for CSF testing when a positive low serum titer is reported. Cryptococcal meningitis should be considered seriously when the CSF CrAg titer is positive.